The Effect Of Coretax, Quality Of Fiscus Services, And Digital Literacy On Individual Taxpayer Compliance - Nadia septi Amelia; Srikalimah; Moch. Wahyudi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of coretax implementation, the quality of tax authorities services, and digital literacy on individual taxpayer compliance. This study focuses on the need to improve taxpayer compliance to support state revenues and the digital transformation in the tax system through the implementation of coretax by the Directorate General of Taxes. In addition, tax authorities services and digital literacy are also considered to play an important role in improving tax compliance in the digital era. To achieve these objectives, this study uses a quantitative approach with a survey approach involving the distribution of questionnaires to individual taxpayers registered at the Kediri City Tax Office (KPP Pratama). The sampling technique uses purposive sampling with the criteria of respondents having a Taxpayer Identification Number (NPWP) and having used coretax. Then the data obtained will be analyzed using multiple linear regression analysis with the help of IBM SPSS Statistics 25 software. The expected results of this study are evidence that coretax implementation, the quality of tax authorities services, and digital literacy have a positive influence on individual taxpayer compliance. Thus, the improvement of the digital-based tax system, optimal tax authorities services, and digital literacy are expected to improve taxpayer compliance in a sustainable manner. Keywords: Coretax, Quality of Tax Service, Digital Literacy, Taxpayer Compliance.